2012
DOI: 10.1088/0034-4885/75/6/066501
|View full text |Cite
|
Sign up to set email alerts
|

The physics of the colloidal glass transition

Abstract: As one increases the concentration of a colloidal suspension, the system exhibits a dramatic increase in viscosity. Beyond a certain concentration, the system is said to be a colloidal glass; structurally, the system resembles a liquid, yet motions within the suspension are slow enough that it can be considered essentially frozen. For several decades, colloids have served as a valuable model system for understanding the glass transition in molecular systems. The spatial and temporal scales involved allow these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
582
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(626 citation statements)
references
References 508 publications
(990 reference statements)
32
582
0
1
Order By: Relevance
“…Crocker & Grier (1996) did an error analysis for the tracking technique employed here and came to the conclusion that the error for locating the objects (BPs in our case) can have a minimum value somewhat better than 0.05 pixel. However, considering the fact that the size and intensity variation of such BPs may affect this precision (Hunter & Weeks 2012), we (over-) estimate that our algorithm is able to locate the BPs within half a pixel (Crocker & Grier 1996).…”
Section: Bp's Location and Its Trajectorymentioning
confidence: 96%
“…Crocker & Grier (1996) did an error analysis for the tracking technique employed here and came to the conclusion that the error for locating the objects (BPs in our case) can have a minimum value somewhat better than 0.05 pixel. However, considering the fact that the size and intensity variation of such BPs may affect this precision (Hunter & Weeks 2012), we (over-) estimate that our algorithm is able to locate the BPs within half a pixel (Crocker & Grier 1996).…”
Section: Bp's Location and Its Trajectorymentioning
confidence: 96%
“…5 Owing to vast academic interest and industrial applications this class of materials has attracted significant attention of the scientific community over the past decade. [6][7][8][9] However inapplicability of fundamental laws of viscoelasticity along with yielding behavior and thixotropy limit the analyzability and optimal applicability of these materials. Recently Joshi and coworkers [10][11][12] showed that fundamental laws of linear viscoelasticity such as …”
mentioning
confidence: 99%
“…In this regard, since crystallization competes with glass formation, a knowledge of the mechanisms that govern the crystal growth in supercooled liquids is considered an important step to elucidate the nature of the glass transition [2-6]. So far, experimental studies aiming at providing microscopic insights into the dynamics and crystallization of supercooled liquids have been largely based on the use of colloidal suspensions [7,8], where the large particle size allows one to follow the crystal growth on the laboratory time scale. However, diverse drawbacks such as polydispersity and sedimentation often make the experimental data from these systems difficult to interpret [8,9].…”
mentioning
confidence: 99%
“…So far, experimental studies aiming at providing microscopic insights into the dynamics and crystallization of supercooled liquids have been largely based on the use of colloidal suspensions [7,8], where the large particle size allows one to follow the crystal growth on the laboratory time scale. However, diverse drawbacks such as polydispersity and sedimentation often make the experimental data from these systems difficult to interpret [8,9]. Accessing the details of the crystallization process in simple atomic and molecular counterparts, on the other hand, remains an experimental challenge due to relevant time scales that are orders of magnitude shorter.…”
mentioning
confidence: 99%